Capitalist and Labor Relations under Islamic Jurisprudence (Al Basirah, 2020)
In the modern world, the issues and challenges between the capitalistand labor relation have been worth importance from last many years.Practically speaking, ensuring the rights and obligations of both parties caneradicate the distances between the two potential economic players.Explicit clauses of contract can build the confidence level of labor andcapital as well which will further stimulate the level of productivity in thecountry rather it will serve as catalyst for the sustainable development. TheGolden means for the capitalist and labor has been highlighted which stemform the foundation laid down in Quran and Hadiths. The maximum clarityin the job contract and assurance of the rights and obligations of theCapitalist and Labor under the umbrella of Islamic Jurisprudence can onlyenhance the healthy and growth oriented environment for all the economicactivities. The main stance of the Islam Golden means is interest of oneparty must not be escalated on the cost of other party.
Keywords: Capitalist, Labor, Rights, Obligation, Islamic Jurisprudence.